PENGARUH CAPITAL INTENSITY DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesa Tahun 2017-2021) - Wizanasari Wizanasari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study aimed to determine the effect of capital intensity and institutional ownership on tax avoidance in empirical studies on food and beverage subsector companies listed on the Indonesia Stock Exchange in 2017-2021. The type of research used is associative-quantitative. The data used in this study was secondary data. The sample selection was carried out based on the purposive sampling method, with a sample of 20 companies that fit the 5 criteria in the study. The documentation method was used to collect data from the Indonesia Stock Exchange and the company’s website. The data analysis techniques used were descriptive statistical analysis and panel data regression. The E-Views program 10 was used to process the data. The result showed that capital intensity and institutional ownership had a simultaneous effect on tax avoidance, meanwhile partially showed that capital intensity and institutional ownership had no effect on tax avoidance had an negative effect on tax avoidance. Keywords: Capital Intensity, Institutional Ownership, Tax Avoidance